Integrated omics profiling of individual variations in intestinal damage to the soybean allergen in piglets - Mi, Mengmeng; Zheng, Yaqing; Fu, Xin; Bao, Nan; Pan, Li; Qin, Guixin; Zhao, Yuan (Frontiers in Veterinary Science, 2025)
IntroductionA small number of soybean allergens [including Glycinin (11S) and β-Conglycinin (7S)] in the commercially available corn-soybean meal diet can still cause allergy in some weaned piglets, which may be the result of the interaction of genetic, and nutrition, but the specific mechanism is still unclear.MethodsIn this study, 20 allergic piglets and 20 non-allergic piglets were selected from 92 weaned piglets by skin sensitization tests, which were used to examine the whole sequence genome. The indicators related to humoral and cellular immunity, transcriptomics, and metabolomics analysis were determined by randomly selecting 5 boars in the allergic group and non-allergic group and then performing a validation in vitro.ResultsThe sensitization rate of soybean antigen in the corn-soybean meal diet was 21.74% and there was a gender difference with the sensitization rate of female pigs (31.34%) being higher than that of male pigs (13.23%). Moreover, the levels of inflammatory factors (IL-1β, IL-4, TNF-α) and antibodies (IgG, IgE, and specific IgG) in allergic piglets were significantly higher than those in non-allergic piglets (P < 0.05). Whole genome re-sequencing analysis revealed specific mutations in the exons and URT5 of TRAPPC2, PIR, CFP, and SOWAHD genes and showed significantly higher expression levels of related genes in the spleen of allergic piglets (P < 0.05). Transcriptome analysis identified IL17REL, CCL19, CD1E, CD1.1, etc. immune differential genes, metabolomics results showed that soybean antigen affected the utilization and metabolism of intestinal nutrients in piglets, mainly the digestion and absorption of protein and the synthesis and metabolism of amino acids. Transfection of CFP/TRAPPC2/CCL19 siRNA could partially alleviate the injury of RAW264.7 cells or IPEC-J2 cells induced by β-Conglycinin.ConclusionTherefore, the individual differences in intestinal damage induced by soybean antigen protein in the corn-soybean meal diet are closely related to PIR, CFP, TRAPPC2, SOWAHD, and CCL19 genes. Soybean antigens affect the intestinal nutrient utilization and metabolism of piglets, which provides a scientific reference for the study of soybean antigen sensitization mechanisms, precision nutrition, disease prevention, and control of piglets, and also lays a foundation for human foodborne diseases.